Drug Utilization Patterns and Pharmacoeconomic Evaluation in Patients Undergoing Abdominal Surgery at a Tertiary Care Hospital - Konnur, Raghavendra; Kumar, Jayanthi Mallappa; Singanahalli, Pankaja Shivaramu; Choudhury, Saddique; Gangadhar, Manu (Indian Journal of Pharmacy Practice)
Background: This study investigates the patterns of medication usage and evaluates the pharmacoeconomic implications of drugs administered during abdominal surgeries in a tertiary care hospital setting. Particular emphasis is placed on two primary therapeutic categories: analgesics and Proton Pump Inhibitors (PPIs). Understanding these patterns aids in optimizing pharmacological decisions and curbing unnecessary healthcare expenditures. Objectives: To assess drug utilization trends and conduct a pharmacoeconomic evaluation among patients undergoing abdominal surgeries. Materials and Methods: A cross-sectional study was conducted on 110 patients receiving perioperative care. Data were extracted from inpatient case records to analyze demographics, prescribing patterns, dosage regimens, duration of therapy, and comparative drug costs. A Cost-Minimization Analysis (CMA) was utilized to evaluate price variations between hospital-supplied drugs and other commercially available brands. Results: Diclofenac (48.18%) and tramadol (47.27%) were the most prescribed analgesics, while pantoprazole (46.36%) was the leading PPI. Substantial price differences were observed, particularly for Inj. Paracetamol 1 g (236.77% cost variation). These discrepancies suggest significant opportunities for reducing costs through rational prescribing and promoting generic alternatives. Conclusion: Rational and cost-conscious drug prescribing is essential for improving patient outcomes and minimizing financial burden. Encouraging the use of generics, enforcing pricing transparency, and implementing evidence-based prescription protocols can significantly enhance affordability and care quality in perioperative settings.
Keywords: Perioperative Pharmacotherapy; Cost Variation Analysis; Generic Substitution; Analgesic Utilization; Proton Pump Inhibitors; Abdominal Surgery Economics